Empowerment Indonesian Migrants Workers through Continuing Education for Better Adaptation in Overseas - Vera Bararah Barid; Rofi Wahanisa; Sri Wahyu Krida Sakti; Purwaningdyah Murti Wahyuni (Universitas Negeri Semarang, 2026)
Indonesian migrant workers encounter significant challenges in adapting to the legal, social, and cultural environments of their destination countries. Limited knowledge of local legal systems and employment regulations often increases their vulnerability to labor exploitation and legal disputes. This study examines the challenges faced by Indonesian migrant workers in the adaptation process and analyzes the role of legal education in strengthening their legal awareness and capacity for social integration. Employing a socio-legal approach, the research utilizes primary data obtained through interviews and institutional information, complemented by secondary data from legislation, academic literature, and relevant policy documents. The findings reveal three key issues. First, Indonesian migrant workers face legal, linguistic, cultural, and socio-economic barriers that hinder effective adaptation in host countries. Second, limited access to legal information and education reduces their ability to understand and exercise their rights and obligations under the legal framework of the destination country. Third, the Continuing Education (CE) Program developed by the Universitas Terbuka for Overseas Students provides an accessible legal education platform that enhances legal literacy, supports social adaptation, and promotes awareness of workers' rights and responsibilities. This study argues that legal education constitutes a preventive mechanism for migrant worker protection by empowering individuals to navigate foreign legal systems and reduce legal vulnerability. It further highlights the importance of state support through accessible and sustainable educational programs as an integral component of migrant worker protection and empowerment.